Evaluating the reality of applying political marketing strategies (A field study on elections for local council members in Latakia Governorate) - معلّا, فؤاد; نهاد نادر; ديمة ماخوس (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to evaluate the reality of applying political marketing strategies within the framework of elections for local council members in Latakia Governorate, since the researcher relied on studying five basic strategies for political marketing (push strategy- pull strategy- wait strategy- timing strategy- consensus building strategy). The researcher relied on the descriptive analytical method, and used the facilitated random sampling method for the study population by distributing (119) questionnaires to citizens who are entitled to cast their electoral votes in the local councils in Latakia Governorate, which were retrieved and fully analyzed through the SPSS program, to test hypotheses, the researcher used the Student T test for one sample. The research found a high level of application of both the push and timing strategies, while the level of application of the consensus building strategy was low, and the sample was neutral regarding the level of application of both the pull and wait strategies. The research concluded with a set of recommendations related to the necessity of planning the political marketing process according to well-studied standards, and determining the political marketing methods that the candidate will use it in his election campaign, in addition to shaping the mental image in a positive way in the media.